Calculation of the ideal plot size for experiments using eucalyptus (Research, Society and Development, 2020)
An adequate experimental planning depends on several factors, such as homogeneity of the area and experimental unity, number of repetition and plot size. The adoption of an ideal plot size reduces the experimental error and, consequently, maximizes the information obtained in an experiment. Thus, the aim of the present study was to calculate the optimal plot size of eucalyptus culture in a greenhouse, in order to optimize labor and costs in the cultivation process of this economically important culture. To calculate the optimal plot size, several simulations were performed using the modified maximum curvature method. Throughout the experimental period, clonal seedlings of the Eurograndis hybrid were used and evaluated for height (H), stem diameter at the base (DB), chlorophyll content in old leaves (Chlor V) and new leaves (Chlor N) at 30, 60, 90 and 120 days after seedling transplantation. After 120 days, the seedlings were collected to determine the dry mass of the aerial part (DMAP) and the root system (DMRS). Results indicated that the optimal recommended plot size for eucalyptus, in a greenhouse, were 6 plants per plot.